Organic fertilizer has a greater effect on soil microbial community structure and carbon and nitrogen mineralization than planting pattern in rainfed farmland of the Loess Plateau - Wang, Yi; Li, Qianxue; Li, Chunyue (Frontiers in Environmental Science, 2023)
Agricultural ecosystem is the largest artificial ecosystem on Earth and provide 66% of the world's food supply. Soil microorganisms are an engine for carbon and nutrient cycling. However, the driving mechanism of soil microbial community structure and carbon and nitrogen transformation mediated by fertilization and planting pattern in rainfed agricultural ecosystems is still unclear. The research was conducted at the Changwu Agricultural Ecology Experimental Station in Shaanxi Province, China. Seven different fertilization and planting pattern were designed. The Phosphate fatty acids (PLFAs) were used to explore the effects of fertilization and plating pattern on the soil microbial community structure and the relationship with soil carbon and nitrogen transformation. The results showed that there were significant differences in soil physical and chemical properties among treatments. Organic fertilizer significantly increased the soil carbon and nitrogen and decreased the soil pH. The contents of total PLFAs and microbial groups in the wheat and corn rotation treatment were the highest. Compared with the change in planting pattern, organic fertilizer had a greater impact on PLFA content and soil ecological processes. The soil microbial community structure has a significantly positive correlation with soil organic carbon (SOC), total carbon (TC), total nitrogen (TN) and total phosphorus (TP). Compared with applying NP fertilizer, applying organic fertilizer significantly increased the soil respiration rate and mineralized nitrogen content while decreasing the soil microbial biomass carbon (MBC). The correlation analysis showed that soil respiration was significantly positively correlated with SOC and TP, and mineralized nitrogen was significantly positively correlated with SOC, nitrate nitrogen, TN and MBC. Structural equation modeling (SEM) showed that the soil respiration rate was significantly positively affected by TC and negatively affected by SWC and explained 63%, whereas mineralized nitrogen was significantly positively influenced by TN and explained 55% of the total variance.